Moxibustion as a Therapy for Breast Cancer–Related Lymphedema in Female Adults: A Preliminary Randomized Controlled Trial - Chunhui Wang PhD; Ming Yang MD; Yingyi Fan PhD; Xiaohua Pei PhD (Integrative Cancer Therapies, 2019)
Objective: To evaluate the effect of moxibustion on relieving breast cancer–related lymphedema. Materials and Methods: A randomized controlled trial was conducted in our institution from March 2016 to March 2017. All patients (N = 48) with cancer-related lymphedema were allocated to 2 groups: a treatment group, in which moxibustion was performed, and a control group, in which pneumatic circulation was performed with compression garments worn every day. Therapeutic efficacy was evaluated by measuring arm circumference (wrist crease, 10 cm proximal to wrist crease, elbow crease, and 10 cm proximal to elbow crease) and determining the Revised Piper Fatigue Scale score and Visual Analog Scale score for swelling before and after treatment. Results: All patients were treated for 4 consecutive weeks. Compared with 0 week after treatment, the affected-side arm circumference after 4 weeks’ treatment decreased in both treatment and control groups; the difference value in the treatment group was superior to that in the control group. Compared with the controls, moxibustion resulted in a lower Visual Analog Scale score. The Revised Piper Fatigue total scores were improved in both the moxibustion and control group, and there was no significant difference between the 2 groups. Moxibustion reduced the behavioral, sensory, emotional, and cognitive Revised Piper Fatigue scores, but only the behavioral and sensory scores improved in the control group. Conclusion: Moxibustion has potential effect on breast cancer–related lymphedema. We present promising preliminary data for larger randomized trials to enable accurate evaluation of moxibustion as a lymphedema treatment.